Study of Potassium KNO3 Concentration Against Growth In Vitro Plantlets of Granola Potato (Solanum tuberosum L.) - Rudi Wardana; Maharani, Jeany Zanti Ayu (KHD Production, 2026)
Tissue culture techniques be one of solution in multiply seed potato quality high. One of the obstacles faced​ in tissue culture potato is growth suboptimal plantlets, such as circumference small and not stem​ Sekulen. Research This study aimed to influence potassium concentration of KNO₃​ to growth plantlets potato Granola varieties in vitro, as well as determine optimal concentration that supports growth best. Research carried out in the Tissue Culture Laboratory Plants , Jember State Polytechnic in June 2024 to finished , using Non- factorial Completely Randomized Design (CRD) with five levels KNO ₃ concentrations (475 mg/L, 950 mg/L, 1425 mg/L, 1900 mg/L, and 2375 mg/L) each of which was repeated four times. Data analysis was carried out using the ANOVA test and continued with BNJ test at 5% and 1% levels . Research results show that KNO ₃ concentration of 475 mg/L provides most significant influence on the length parameter books and length root plantlets. Therefore that, concentration the can recommended as optimal dose for increase growth plantlets Granola potatoes in vitro.